Adaptação transcultural e validação do instrumento clear communication index (CDC-CCI) para a língua portuguesa do Brasil - Angélica Maria Cupertino Lopes Marinho (2020)
Educational and informational materials in health, to promote health, must be understood by the final public. In order to qualify the elaboration and evaluation of health communication materials, the Clear Communication Index instrument of the Centers for Disease Control and Prevention (CDC-CCI) was created. It consists of 20 multiple-choice questions that mark presence or absence of criteria for clarity of communication, distributed in seven domains: "Main Message and Call to Action", "Language", "Information Design", "State of Information" Science "," Behavioral Recommendations "," Numbers "and" Risk ". The objective was to adapt cross-culturally and validate the CDC-CCI for the Portuguese language of Brazil. In the cross-cultural adaptation, the semantic equivalences (composed of equivalences of referential and general meanings) and conceptual equivalences were evaluated through translations, synthesis of translations, back-translations and pre-tests. For referential meaning, equivalence was judged on a visual analog scale from 0 to 100%, considering “non-equivalence” (<80%), “almost equivalence” (80-89%) and “maximum equivalence” (90-100 %). The general meaning was considered to be "Unchanged" (UC), "Little Changed" (LC), "Very Changed" (VC) or "Completely Changed" (CC). Then, conceptual equivalence was sought through the pre-test by applying the pre-final version in educational material, by 30 professionals with a higher level of primary care in public health, reaching the adapted version. The adapted instrument was applied, by 105 other public health professionals, in the same educational material, with a view to the analysis of psychometric properties. 30% of these 105 professionals retested 15 to 20 days later to test the temporal stability using Kappa Cohen intra-examiner concordances. At the same time, a committee of experts evaluated the same educational material, constituting the gold standard. The positive responses of the evaluators were compared to those of the gold standard and described in the area under the ROC curve (IC95) and in sensitivity tests. Demographic and professional data were collected by questionnaire. The information was recorded by double entry and analyzed in the STATA Program. In the first phase, the average age of professionals was 36.8 years, 87% were women (87%) and 77% were dentists and nurses. In the second phase, the average age was 35.6 years, 77% women and 71% dentists and nurses. General equivalence was maintained in 15 of the 20 items (75%), three items remained little changed (15%) and one of them was very changed (10%). Nineteen items showed maximum referential equivalence or almost equivalence (95%). The highly altered item, after submission to the committee, was considered, by consensus, adapted. The reproducibility in eighteen questions (90.0%) had a Kappa value equal to 1 (almost perfect agreement), in one question (5.0%) the Kappa was 0.839 (substantial agreement) and one question (5.0 %), 0.570 (moderate agreement). The area under the ROC curve for the nineteen questions considered applicable by the gold standard, was 0.9412 (CI 95% - 0.8259-1,000). In the four simulations performed, which included a question considered not applicable by the gold standard, the area values under the curve were greater than or equal to 0.6275. The CDC-CCI presented in its Brazilian version (BR-CDC-CCI) equivalence with the original version in addition to validity and reliability for use in the Brazilian context.